Psychometric properties of the Sport Anxiety Scale-2 for Chinese adolescent athletes taking the National Sports College Entrance Examination - Li, Shichen; Tang, Changfa; Guo, Cheng; Bu, Te (Frontiers in Pediatrics, 2023)
Background: This study aims to evaluate the psychometric properties of the Sport Anxiety Scale-2 (SAS-2) in Chinese adolescent sports exam candidates. Methods: One day before the National Sports College Entrance Examination, 965 Chinese athletes rated the Chinese-language SAS-2. Confirmatory factor analysis was performed to test the three-factor structure. Factorial invariance was tested by comparing the configural invariance model to three more constrained models. Construct validity and reliability were determined. Results: Fit indices meet the critical values: CFI = 0.953, TLI = 0.943, RMSEA = 0.048 [90% CI, 0.041 to 0.054], and SRMR = 0.042. All path factor loadings exceed 0.5. The changes in CFI and RMSEA across the configural, metric, scalar, and uniqueness invariance are within the critical values, demonstrating strict measurement invariance across gender, years of training, and type of sports. The average variance extracted of the worry sub-scale is above the cutoff criteria, and McDonald's omega coefficients are over 0.70. Significant correlations exist between the SAS-2, SCAT, and CSAI-2. Factor correlations are all below 0.8. The measurement also distinguishes the known gender effect, with females showing a probability of 58.6% higher anxiety levels. The intraclass correlation coefficient ranges from 0.706 to 0.801.This study validated the Chinese-language SAS-2 in measuring competitive anxiety among Chinese adolescent athletes taking the National Sports College Entrance Examination. The development of the scale's applicability in China is discussed.